The effects of a hybrid negative income tax on poverty and inequality: A microsimulation on the UK and Italy - Alexander Tromp (University of Essex, Institute for Social and Economic Research (ISER), 2017)
This paper aims to propose a social protection system that "decommodifies" labour and fulfills the properties of a Social Protection Floor satisfying revenue-neutrality. To this end, firstly, a Universal Basic Income (UBI) scheme is explored. Secondly, the UBI is transformed into a Negative Income Tax (NIT) scheme, providing universal protection instead of universal benefits. Finally, the NIT is modified into a Hybrid NIT (HNIT), being a mixture of NIT and a classic social assistance scheme. It features a 100% withdrawal rate, consequently allowing for a higher guaranteed minimum income level than would be possible with either an NIT or UBI. A static microsimulation, using the EUROMOD model, is conducted on the HNIT scheme, implementing two scenarios. One scenario establishes what the maximum levels of entitlements could be, assuming revenue-neutrality and current marginal tax levels. The other scenario assumes more generous entitlements and computes which tax rates would be necessary to pay for such a scheme. The models are applied to both Italy and the United Kingdom. The results are interpreted in terms of poverty and inequality statistics while closely looking into the assumptions of the microsimulation models. In the first scenario a modest level of guaranteed minimum income is feasible, decreasing both poverty and inequality decidedly compared to current levels. This effect is even stronger in the second scenario, however, it results in unrealistically high tax rates, especially for Italy. The impact on poverty and inequality of the HNIT scheme is markedly higher for Italy in both scenarios suggesting that the United Kingdom has currently a social protection system in place that redistributes more efficiently than Italy.
Keywords: D31; H23; H53; I38; 330; social protection policy reform; tax-benefit system reform; static microsimulation; income inequality and poverty; work incentives; negative income tax